Complete Genome Sequences of emm6 Streptococcus pyogenes JRS4 and Parental Strain D471 - Port, Gary C. (Genome Announc, 2015)
We report the complete genome assemblies of the group A Streptococcus pyogenes serotype emm6 strain D471 and its streptomycin-resistant derivative JRS4. Both of these well-studied laboratory strains have been extensively characterized over the past three decades and have been instrumental in the discovery of multiple aspects of streptococcal pathogenesis.